Future Perfect? The Future of the Social Sciences in Public Health - Shelton, Rachel C.; Hatzenbuehler, Mark L.; Bayer, Ronald; Metsch, Lisa R. (Frontiers in Public Health, 2018)
This is a critical and perhaps unprecedented time for the social sciences in public health. While there are many opportunities for the social sciences to continue making transformative contributions to improve population health, there are significant challenges in doing so, particularly in a rapidly changing political landscape. Such challenges are both external (e.g., congressional calls for reducing social science funding) and internal (e.g., scholars criticizing the social sciences for being stagnant and siloed). This paper highlights four key tensions that the field is grappling with and that have direct implications for how to train the next generation of social scientists in public health. We also discuss how departmental and institutional decisions made in response to these tensions will determine how the social sciences in public health are ultimately recognized, sustained, and advanced.